The use of the Eurosystem's monetary policy instruments and operational framework since 2009 - Fabian Eser; Marta Carmona Amaro; Stefano Iacobelli; Marc Rubens (European Central Bank (ECB), 2012)
This paper provides a comprehensive overview of the use of the Eurosystem's monetary policy instruments and the operational framework from the first quarter of 2009 until the second quarter 2012. The paper discusses in detail, from a liquidity management perspective, the standard and non-standard monetary policy measures taken over this period. The paper reviews the evolution of the Eurosystem balance sheet, participation in tender operations, the outright purchase programmes, patterns of reserve fulfilment, recourse to standing facilities as well as the steering of money market interest rates.
Keywords: E31; E41; E58; E62; 330; central bank liquidity managem.; central bank operational framework; monetary policy implementation; Geldpolitik; Offenmarktpolitik; Wechselkurspolitik; Mindestreserve; Eurozone